Pengabdian Kepada Masyarakat Mahasiswa Universitas Internasional Batam di Masjid Baitul Muttaqin Batam - Nurfadhilah Huraiyah Masayu; Aulia Nurul Afiza; Muhammad Salman Alfarisi; Nabila Rasya; Muhammad Fahri Yuatama; Diviani Meistari; Erfira Ananda Talia (ConCEPt - Conference on Community Engagement Project, 2025)
This community service activity aims to guide the children of TPQ Baitul Muttaqin in Tiban Impian in studying/memorizing the Qur'an and practicing the knowledge they have learned. The activity was carried out in the form of providing motivation on the virtues of studying the Qur'an, conducting a question and answer session, memorizing hadiths about the virtues of studying the Qur'an, and applying the morals of the Qur'an to the children. The results of the activity showed an increase in the children's awareness and enthusiasm for studying the Qur'an and the students' ability to guide and teach the Qur'an to them. What is unique about this activity is the high enthusiasm of children of various ages, some children still have difficulty writing and following dictation, but they still show seriousness and high enthusiasm in learning. To ensure the program continues to run, a "Qur'an reading equipment box" can be prepared containing Iqra' books, hijaiyah letter posters, and the Qur'an which is stored in the mosque, so that it can be used directly by the children and future teachers.